Practicing forensic anthropology a human rights approach to the global problem of missing and unidentified persons - Kimmerle, Erin H.; Himmelgreen, David Allen; Kedia, Satish; National Association for the Practice of Anthropology (Hoboken, New Jersey Wiley Subscription Services, Incorporated, 2014)
The problem of missing, endangered, and unidentified persons is increasingly approached through a human rights model with successful outcomes. Contexts vary from international investigations into war crimes, genocide, and extrajudicial killings to American "cold cases." In all these examples, anthropologists play critical roles such as searching for clandestine graves, crime scene recovery, human identification, interviewing witnesses, repatriation, public education, and testifying in court. To successfully identify unknown persons, key questions about human variation and biology are essential. For example, can ancestry be reliably estimated? What are the ramifications of estimating the biological profile of an unknown person without appropriate references samples? Does the variation occur because of inherent genetic variation or environmental conditions? Given the potential variation that exists, what are the implications of using standard calibrations across populations in criminal trials? Moreover, forensic anthropologists today work in diverse cultural and legal environments. How do the roles of forensic anthropologists differ in diverse legal settings? The current practice of forensic anthropology ranges from field to lab to courtroom and has evolved as a discipline from what it was almost a century ago. The purpose of this volume is to explore the ways in which forensic anthropology intersects with current human right and humanitarian justice initiatives. The 11 papers in this series include a range of emerging new tools and approaches to human identification and the investigation of long-term missing and unidentified persons.--Publisher's description.
Practicing forensic anthropology: a human rights approach to the global problem of missing and unidentified persons / Erin H. Kimmerle -- Forensic anthropology in long-term investigations: 100 cold years / Erin H. Kimmerle -- Where are they? missing, forensics, and memory / Jose Pablo Baraybar and Rebecca Blackwell -- Ignorance is not bliss: evidence of human rights violations from civil war spain / Derek Congram, Ambika Flavel, and Kim Maeyama -- Human rights investigations in Spain / Roxana Ferllini -- Intersite analysis of victims of extra- and judicial execution in civil war Spain: location and direction of perimortem gunshot trauma / Derek Congram, Nicholas Passalacqua, and Luis Ríos -- Trauma patterns in cases of extrajudicial executions / Erin H. Kimmerle and John Obafunwa -- Toward estimating geographic origin of migrant remains along the United States-Mexico border / M. Katherine Spradley -- Craniometric variation of diverse populations in florida: identification challenges within a border state / Meredith L. Tise, Erin H. Kimmerle, and M. Katherine Spradley -- Application of stable isotope forensics for predicting region of origin of human remains from past wars and conflicts / Eric J. Bartelink, Gregory E. Berg, Melanie M. Beasley, and Lesley A. Chesson -- Georeferencing a cold case victim with lead, strontium, carbon, and oxygen isotopes / George D. Kamenov, Erin H. Kimmerle, Jason H. Curtis, and Darren Norris -- Contributions of radiocarbon analysis in human rights investigations / Douglas H. Ubelaker.
"Annals of Anthropological Practice is published by Wiley Blackwell for the National Association for the Practice of Anthropology, a section of the American Anthropological Association."--Back cover.
Includes bibliographical references.
Keywords: Forensic anthropology; Forensic sciences; Human remains (Archaeology)